Repérage et anatomie du secteur de l’économie circulaire au Sénégal - Serigne Momar Sarr (VertigO)
This article critically explores the political and institutional reality of the circular economy in Senegal and its scaling up through waste recycling and recovery. Despite the opportunities offered by the circular economy in waste management, the Senegalese government has not yet set up an institutional mechanism to promote and drive the sector. Instead, it is the Technical and Financial Partners (TFPs) and local initiatives by social and economic entrepreneurs that are working to develop the sector. The article is more of a theoretical reflection, supplemented by a number of interviews with resource persons. Documentary analysis plays an important role, as does discussion. At the end of this work, it is established that the concept of the circular economy does not appear explicitly in Senegal's development framework. However, this does not prevent the sector from existing, particularly through the TFPs thanks to North-South cooperation and local initiatives to promote and develop the circular economy through organizations and local authorities. Scaling up the circular economy as an alternative to the accumulation of waste therefore remains a growing challenge.